A survey on clinical communication competence of psychiatric nurses in Guangdong Province (广东省精神科护士临床沟通能力调查分析) - LI Xiaochan (李晓婵); ZHUANG Jingyi (庄静仪); ZHANG Huixian (张慧娴); XIE Jiao (谢姣); HAO Li (郝丽); LUO Juanjuan (罗娟娟); ZENG Junfang (曾君芳); ZOU Caimei (邹彩媚) (Association of Integrative Nursing, 2021)
Objective To investigate the clinical communication competence of psychiatric nurses in Guangdong Province and its influencing factors, and provide reference for the improvement of communication skills among psychiatric nurses. Methods A cross-sectional study using general information scale and the Clinical Communication Competency Scale (CCCS) was conducted to 667 psychiatric nurses in Guangdong Province. Results The total score of CCCS was (3. 99±0. 57) , dimensions arranged by scores from the highest to the lowest were: team communication (4. 15±0. 62), verbal communication (4. 01±0. 59), affective perception (4. 00±0. 60), Non-verbal communication (3. 99±0. 61), emotional support (3. 95±0. 63) and communication in difficult situations(3. 92±0. 60). The main factors influencing the clinical communication competence of psychiatric nurses were age, professional title, job title and job seniority (P<0. 05). Conclusion Findings of the study indicated a high level of team communication competence of psychiatric nurses , however relatively low level of emotional support and communication in difficult situations were found. Targeted training program should be carried out to improve the clinical communication competence of psychiatric nurses in Guangdong Province (目的 调查广东省精神科护士的临床沟通能力水平并分析其影响因素, 为管理层提高精神科护士沟通能力提供参考依据。方法 采用方便抽样的方法, 使用一般资料问卷及临床沟通能力量表对广东省31所医院667名精神科护士进行横断面调查。结果 广东省精神科护士的沟通能力总分为(3. 99±0. 57)分。各维度得分从高到低依次是团队沟通能力(4. 15±0. 62)分, 基本语言沟通能力(4. 01±0. 59)分, 情感感知能力(4. 00±0. 60)分, 基本非语言沟通能力(3. 99±0. 61)分, 情感支持能力(3. 95±0. 63)分, 困难情景沟通能力(3. 92±0. 60)分。精神科护士的年龄、职称、职务及工作年限是影响其临床沟通能力得分的主要因素, 差异具有统计学意义(P<0. 05)。结论 广东省精神科护士的团队沟通能力较好, 但情感支持和困难情景沟通能力较弱, 提示医院管理层需要针对性地进行沟通能力培训, 从而提高精神科护士的临床沟通能力。)